Systemic elastin degradation in chronic obstructive pulmonary disease. Issue 7 (28th February 2012) - Maclay, John D; McAllister, David A; Rabinovich, Roberto; Haq, Imran; Maxwell, Scott; Hartland, Stephen; Connell, Martin; Murchison, John T; van Beek, Edwin J R; Gray, Robert D; Mills, Nicholas L; MacNee, William
Abstract : Background: Development of emphysema and vascular stiffness in chronic obstructive pulmonary disease (COPD) may be due to a common mechanism of susceptibility to pulmonary and systemic elastin degradation. Objectives: To investigate whether patients with COPD have evidence of systemic elastin degradation in the skin. Methods: The authors measured cutaneous elastin degradation using immunohistochemistry (percentage area of elastin fibres) in sun-exposed (exposed) and non-sun-exposed (non-exposed) skin biopsies in 16 men with COPD and 15 controls matched for age and cigarette smoke exposure. Quantitative PCR of matrix metalloproteinase (MMP)-2, -9, -12 and tissue inhibitor of metalloproteinase-1 mRNA and zymography for protein expression of MMP-2 and -9 were performed on homogenised skin. Arterial stiffness and emphysema severity were measured using carotid-femoral pulse wave velocity and quantitative CT scanning. Results: Skin elastin degradation was greater in exposed and non-exposed skin of patients with COPD compared with controls (exposed, mean (SD); 43.5 (12.1)% vs 26.3 (6.9)%, p<0.001; non-exposed 22.4 (5.2)% vs 18.1 (4.3)%, p=0.02). Cutaneous expression of MMP-9 mRNA and proMMP-9 concentrations was increased in exposed skin of COPD patients (p=0.004 and p=0.02, respectively) and was also associated with increased skin elastin degradation (r=0.62, p<0.001 and r=0.47, p=0.01, respectively). In the entire cohort of ex-smokers, cutaneous elastin degradation was associated with emphysema severity, FEV1 and pulse wave velocity. Conclusions: Patients with COPD have increased skin elastin degradation compared with controls, which is related to emphysema severity and arterial stiffness. Systemic elastin degradation due to increased proteolytic activity may represent a novel shared mechanism for the pulmonary, vascular and cutaneous features of COPD.